Cape Verde : Growth and Poverty Reduction Strategy Paper II (2008-11) Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper-II for Cape Verde. Important progress was made in poverty reduction, but rural poverty still remains high. The strategy reports that Cape Verde is on track to meet the Millennium Development Goal of halving extreme poverty by 2015. Despite progress made to date, the gap between urban and rural income growth is still wide; thus, efforts to raise rural incomes further and a more effective design of social inclusion programs are needed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet